Cross-disciplinary applications of artificial intelligence and pattern recognition advancing technologies - Mago, V. K.; Bhatia, Nitin, 1978-.; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
'This book provides a common platform for researchers to present theoretical and applied research findings for enhancing and developing intelligent systems, discussing advances in and applications of pattern recognition technologies and artificial intelligence'--
25. A new optimization approach to clustering fuzzy data for type-2 fuzzy system modeling / Mohammad Hossein Fazel Zarandi and Milad Avazbeigi -- 26. Estimation of MIMO wireless channels using artificial neural networks / Kandarpa Kumar Sarma and Abhijit Mitra -- 27. A novel 3D approach for patient schedule using multi-agent coordination / E. Grace Mary Kanaga, M.L. Valarmathi and Preethi S.H. Darius -- 28. A fuzzy approach to disaster modeling: decision making support and disaster management tool for emergency medical rescue services / Jan Stoklasa -- 29. Fuzzy cognitive map reasoning mechanism for handling uncertainty and missing data: application in medical diagnosis / Elpiniki I. Papageorgiou -- 30. On the use of fuzzy logic in electronic marketplaces / Kostas Kolomvatsos and Stathes Hadjiefthymiades -- 31. A neuro-fuzzy expert system trained by particle swarm optimization for stock price prediction / Mohammad Hossein Fazel Zarandi, Milad Avazbeigi and Meysam Alizadeh -- 32. Hand tremor prediction and classification using electromyogram signals to control neuro-motor instability / Koushik Bakshi ... [et al.].
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed January 23, 2012).
Keywords: Pattern recognition systems; Artificial intelligence; Computer vision; Document image analysis; Face recognition; Genetic algorithms; Intelligent tutoring systems; Medical image analysis; Multi agent systems; Natural language processing; Neural networks; Pattern recognition for bioinformatics